Uncovering the Appeal of Bukit Lubang Kilat: Factors Shaping Tourist Visits in Delang Subdistrict - Monicha, Evana Saskia; Zakiah, Wiwin; Beatris, Diana; Sabirin, Sabirin; Tiawon, Harin; Simamora, Lamria; Tuah, Sunaryo N. (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2025)
This study investigates the effect of travel costs, income, distance, and age on the number of tourist visits to Bukit Lubang Kilat, a natural tourism destination located in Delang Subdistrict, Lamandau Regency. Employing a quantitative descriptive approach, the research was conducted over the period of February to March 2023. Primary data were gathered directly from visitors and analyzed using multiple linear regression with the support of SPSS software. The findings reveal that travel cost and distance have a negative and statistically significant effect on the number of visits, indicating that higher expenses and longer distances discourage tourists from visiting. In contrast, income has a positive and significant effect, suggesting that individuals with higher income levels are more likely to visit the destination. The age variable, however, shows no significant effect, indicating that tourist age does not substantially influence their decision to visit Bukit Lubang Kilat. Despite age being insignificant individually, the simultaneous test results indicate that travel costs, income, distance, and age collectively have a significant influence on tourist visit numbers. These results emphasize the importance of economic and geographical considerations in tourism planning, especially in remote or rural areas. To enhance tourist attraction to Bukit Lubang Kilat, local governments and tourism managers should focus on reducing travel-related burdens by improving access, infrastructure, and offering incentives. Additionally, marketing strategies should target higher-income tourists while ensuring affordability and accessibility for broader segments. This research contributes to understanding the determinants of tourist behavior in rural tourism contexts and supports evidence-based policy for sustainable tourism development.